2016
DOI: 10.3866/pku.whxb201609231
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions between Quaternary Ammonium Cationic Surfactants and Bovine Serum Albumin

Abstract: UV-visible (UV-Vis) absorption spectroscopy, fluorescence spectroscopy (FL), dynamic light scattering (DLS) and isothermal titration calorimetry (ITC) were used to study the interactions between bovine serum albumin (BSA) and the three quaternary ammonium surfactants N-dodecyl-N-(2-hydroxyethyl)-N,Ndimethyl ammonium bromide (DHDAB), N-tetradecyl-N-(2-hydroxyethyl)-N,N-dimethyl ammonium bromide (THDAB) and N-cetyl-N-(2-hydroxyethyl)-N,N-dimethyl ammonium bromide (CHDAB). These surfactants quenched the intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…The fluorescence intensity of Trp residues was significantly higher than that of Tyr residues, indicating that the main contribution of the intrinsic fluorescence of BSA is due to the Trp residues, thus DMM-11 and DMPM-11 mainly interact with Trp residues of BSA. These results are similar to those reported for the fluorescence intensity changes of BSA with quaternary ammonium cationic surfactants [39]. Furthermore, Wu and co-workers observed that the fluorescence intensity increases significantly with the increase of cationic gemini surfactants concentrations, when was set at 20 nm [31].…”
Section: Fluorescence Measurementssupporting
confidence: 89%
“…The fluorescence intensity of Trp residues was significantly higher than that of Tyr residues, indicating that the main contribution of the intrinsic fluorescence of BSA is due to the Trp residues, thus DMM-11 and DMPM-11 mainly interact with Trp residues of BSA. These results are similar to those reported for the fluorescence intensity changes of BSA with quaternary ammonium cationic surfactants [39]. Furthermore, Wu and co-workers observed that the fluorescence intensity increases significantly with the increase of cationic gemini surfactants concentrations, when was set at 20 nm [31].…”
Section: Fluorescence Measurementssupporting
confidence: 89%